Предмет: Алгебра,
автор: Егор222202
Решить уравнение:
4(3у+1)^2-27=(4y+9)(4y-9)+2(5y+2)(2y-7)
Ответы
Автор ответа:
0
4(3y)²-27=(4y+9)(4y-9)+2(5y+2)(2y-7)
4(9y²+6y+1)-27=16y²-81+(10y+4)(2y-7)
36y²+24y+4-27=16y²-81+20y²-70+8y-28
36y²+24y-23=36y²-109-62y
24y-23=-109-62y
24y+62y=-109+23
86y=86
y=1
4(9y²+6y+1)-27=16y²-81+(10y+4)(2y-7)
36y²+24y+4-27=16y²-81+20y²-70+8y-28
36y²+24y-23=36y²-109-62y
24y-23=-109-62y
24y+62y=-109+23
86y=86
y=1
Похожие вопросы
Предмет: Окружающий мир,
автор: dimamix135
Предмет: Русский язык,
автор: natala1975kozenenko
Предмет: Биология,
автор: 04vasilisa05
Предмет: Биология,
автор: dddgtrgjgrgh
Предмет: Математика,
автор: bezzubov41